The Effect of Structured Dyadic on the Students' Reading Comprehension - Wardani, Paramita; Agustina, Hiqma Nur; Sudarmaji, Imam (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2022)
The purpose of this study is to determine whether the structured dyadic technique has a substantial impact on the students' reading comprehension in the tenth grade at SMAN 14 Kab. Tangerang This study employed a quantitative approach using a quasi-experimental methodology. This indicates that the author employed two classes, one of which served as the experimental class and the other as the control class. All tenth grade students as well as 72 additional pupils make up the population of this study because purposive sampling was employed to select the sample. The t-test formula was used to test the hypothesis data. As a consequence of the hypothesis test, it was determined that the Sig. is 1.667>0.05, which indicates that Ho is rejected and Ha is accepted. Based on the findings, it can be said that the Structured Dyadic Method (SDM) has a significant impact on the students' reading comprehension in the tenth grade of SMAN 14 Kab. Tangerang.